2022
DOI: 10.1093/rap/rkac097
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural epidemiology of sedentary behaviour in inflammatory arthritis: where are we, and where do we need to go?

Abstract: In the last decade, studies into sedentary behaviour in inflammatory arthritis have raised important questions regarding its role in this condition. Specifically, evidence is needed on whether sedentary behaviour might exacerbate adverse inflammatory arthritis outcomes, and whether reducing sedentary behaviour might offer an effective avenue for self-management in this population. Research exploring these important research questions is still very much in its infancy and lacks the direction and scientific rigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…In addition, Haider et al [ 20 ] showed that levels of accelerometer-assessed MVPA increased two-fold in individuals with a lower clinical disease burden (e.g., lower disease activity, pain intensity and functional disabilities). Further, a recent review highlighted pain, fatigue and compromised physical function as determinants of MVPA in RA, and suggested that such symptoms are less likely to hinder reductions in sedentary time and increases in overall PA (including LPA) in this patient group [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Haider et al [ 20 ] showed that levels of accelerometer-assessed MVPA increased two-fold in individuals with a lower clinical disease burden (e.g., lower disease activity, pain intensity and functional disabilities). Further, a recent review highlighted pain, fatigue and compromised physical function as determinants of MVPA in RA, and suggested that such symptoms are less likely to hinder reductions in sedentary time and increases in overall PA (including LPA) in this patient group [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessing physical activity levels in individuals with arthritis is challenging [46]. In addition, evidence regarding whether sedentary behavior worsens the outcomes of arthritis or whether increasing physical activity is beneficial is lacking [47].…”
Section: Discussionmentioning
confidence: 99%
“…Minimizing sedentary behaviour provides health benefits and might offer another promising management approach for people with RA [ 8 , 28 , 29 ]. Fenton et al [ 30 ] draw on the five-phase behavioural epidemiology framework to summarize the current evidence on the role and mitigation of sedentary behaviour in people with inflammatory arthritis [ 31 ]. They highlight the sporadic nature and mixed quality of research targeting sedentary behaviour, gaps in our understanding, and a lack of causal, experimental research to inform effective intervention approaches.…”
Section: Helping People With Inflammatory Arthritis To Move Morementioning
confidence: 99%
“…They highlight the sporadic nature and mixed quality of research targeting sedentary behaviour, gaps in our understanding, and a lack of causal, experimental research to inform effective intervention approaches. A systematic approach to future investigations is recommended [ 30 ].…”
Section: Helping People With Inflammatory Arthritis To Move Morementioning
confidence: 99%